Association of cardiovascular risk factors and lifestyle behaviors with aortic aneurysm: A Mendelian randomization study - Zhou, Jiawei; Lin, Jianfeng; Zheng, Yuehong (Frontiers in Genetics, 2022)
Abstract Objective: To examine the causality between hypertension, diabetes, other cardiovascular risk factors, lifestyle behaviors and the aortic aneurysm among patients of European ancestry. Methods: We performed Two-Sample Mendelian Randomization (MR) analysis to investigate the causality of 12 modifiable risk factors with aortic aneurysm, including hypertension, body mass index (BMI), waist-hip ratio (WHR), diabetes, tobacco smoking, alcohol and coffee consumption, physical activity, and sleep duration. Genome-wide significant genetic instruments (P < 5×10-8) for risk factors were extracted from European-descent genome-wide association studies (GWAS), while aortic aneurysm genetic instruments were selected from the UK Biobank and FinnGen Cohort. The inverse-variance weighted MR was used as main analysis, and MR-Egger, weighted median MR, MR-PRESSO, and Phenoscanner searching were performed as sensitivity analyses. Further, we calculated MRE intercept to detect pleiotropy and Cochran's Q statistics to assess heterogeneity, and conducted bidirectional MR and MR Steiger tests to exclude the possibility of reverse causality. Results: We observed significantly higher risks for the aortic aneurysm in hypertension (pooled OR: 4.30 [95%CI 2.84–6.52]), BMI (OR: 1.58 [95%CI 1.37–1.81]), WHR (OR: 1.51 [95%CI 1.21–1.88]), WHR adjusted for BMI (WHRadjBMI) (OR: 1.35 [95%CI 1.12–1.63]), age of smoking initiation (OR: 1.63 [95%CI 1.18–2.26]), and tobacco use (initiation, cessation, and heaviness) (OR: 2.88 [95%CI 1.85–2.26]). In sensitivity analysis, the causal effects of hypertension, BMI, WHRadjBMI, and tobacco use (initiation, cessation, and heaviness) remained robust. Conclusions: There was a positive causal relationship between hypertension, BMI, WHR, WHRadjBMI, and aortic aneurysm.